2011
DOI: 10.1002/dvg.20726
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans meg‐1 and meg‐2 differentially interact with nanos family members to either promote or inhibit germ cell proliferation and survival

Abstract: Summary: The closely related C. elegans MEG-1 and MEG-2 proteins localize to P granules during a brief period of embryogenesis when the germ lineage is being separated from the soma. Embryonic primordial germ cells still develop in the absence of MEG activity, but major defects emerge during larval stages when germ cells fail to proliferate or differentiate normally, resulting in sterility. To investigate meg-1 function, we conducted a targeted RNAi screen for enhancers and suppressors of meg-1 sterility. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Interestingly, meg-1 interacts genetically with nos-2. nos-2(RNAi);meg-1(vr10) animals show the most severe phenotype reported for Z2 and Z3: the cells never proliferate, lose perinuclear P granules, and die by the first larval stage in an apoptosis-independent manner (Kapelle and Reinke 2011). Since MEG-1 and NOS-2 expression overlaps only in P 4 , events critical for germ cell fate specification likely occur first in this cell.…”
Section: 3 Molecular Mechanisms Of Germ Cell Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, meg-1 interacts genetically with nos-2. nos-2(RNAi);meg-1(vr10) animals show the most severe phenotype reported for Z2 and Z3: the cells never proliferate, lose perinuclear P granules, and die by the first larval stage in an apoptosis-independent manner (Kapelle and Reinke 2011). Since MEG-1 and NOS-2 expression overlaps only in P 4 , events critical for germ cell fate specification likely occur first in this cell.…”
Section: 3 Molecular Mechanisms Of Germ Cell Specificationmentioning
confidence: 99%
“…MEG-1 does not contain any recognizable RNA-binding motif, but shows complex genetic interactions with RNA-binding proteins that function during larval germline development (Leacock and Reinke 2008; Kapelle and Reinke 2011). One possibility is that RNA regulation by the MEGs and other germ plasm components initiates the network of protein–RNA regulation that drives germ cell proliferation (see Chap.…”
Section: 3 Molecular Mechanisms Of Germ Cell Specificationmentioning
confidence: 99%
“…MEG‐1 and MEG‐2 are partially redundant, novel proteins transiently associating with P‐granules in P2 to P4 germ cells. Similar mutant phenotypes may indicate that nos and meg genes contribute to the same regulatory process, and indeed meg‐1 and nos‐2 genetically interact; the double meg‐1 ; nos‐2 mutant has a more severe phenotype that each of the single mutants (Kapelle and Reinke, ). Z2 and Z3 PGCs in the meg‐1 ; nos‐2 embryos never proliferate, disperse perinuclear P‐granules into the cytoplasm, and die by the first larval stage.…”
Section: Functions In Developmentmentioning
confidence: 94%
“…Z2 and Z3 PGCs in the meg‐1 ; nos‐2 embryos never proliferate, disperse perinuclear P‐granules into the cytoplasm, and die by the first larval stage. Germ cell death in this class of mutants is carried out by a combined effect of apoptosis and an independent “death program” (Subramaniam and Seydoux, ; Kapelle and Reinke, ). Although the germ cells in these mutants are recognizable by the localization of maternally inherited P‐granule components, it is not clear if the zygotic program of germ cell specification is fully intact.…”
Section: Functions In Developmentmentioning
confidence: 99%
“…In C. elegans, the redundant nanos homologs nos-1 and nos-2 are expressed sequentially in PGCs during the maternal-to-zygotic transition and may have overlapping yet distinct effects on mRNAs stability and translation. Genetic analyses already have suggested that nos-1 and nos-2 have both unique and shared functions (Kapelle and Reinke, 2011;Mainpal et al, 2015). It will be important to determine whether nos-1 and nos-2 are both required to keep LIN-15B levels low throughout embryogenesis, and whether they act directly on the lin-15B RNA or indirectly, by silencing other factors required for LIN-15B protein translation and/or stability.…”
Section: Nanos Activity Is Required For the Timely Turnover Of Maternmentioning
confidence: 99%